The Stock System of Contraceptive Devices at the Website-Based BKKBN of Langkat - Muflihan; Sri Wahyuni (Institute of Computer Science (IOCS), 2022)
The inventory recording system manually has various obstacles and weaknesses, so it requires processing inventory data with a website-based information system. The Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) is an Indonesian Non-Departmental Government Institution in charge of carrying out government duties in the field of family planning and prosperous families throughout Indonesia. One of the BKKBN programs is to socialize and distribute contraceptives for Indonesian family planning. Contraceptive devices from the center will then be circulated per sub-district in Langkat Regency. In distributing contraceptives in Langkat district, based on reports from each sub-district in Langkat district. User data and demand for each sub-district are still not evenly distributed so that an application program is needed, namely the design of stockpiles of contraceptives in the use of the family planning program which has problems, because there are often orders for contraception for supplies that are not in accordance with the conditions in the field so that contraception accumulates and is not divided into groups. every district. Inventory data processing at the Langkat Regency BKKBN Office is still manual with recording and processing data using a report book, a website-based Information System is needed. The information system that is designed based on the website can make it easier for users, namely admins and leaders to input data, obtain reports with an internet connection that can be accessed anywhere and anytime. Information system built using PHP programming language with MySQL database. The purpose of this research is to build a system to help BKKBN Langkat.